Some types of problems from probability theory - Giorgadze, Teimuraz (International Scientific Conference “EDUCATION, RESEARCH, PRACTICE” Proceedings, 2024)
In the article, we discussed the structure of the space of elementary motions of the discrete type in the problem of placing n particles in the partition M. We deal with such problems in statistical physics, when studying the distribution of n particles (these can be protons, neutrons or other particles) in M ​​states (these can be energy levels). We have considered several tasks of different types and have calculated all the sesaslo elementary movement quantities.